(untitled) (Journal of the College of Basic Education, 2023)
((O Allah, may blessings and peace be upon our master Muhammad, with whom breasts are opened and matters are easy, and upon his family and companions and peace))Basra had an important impact on the life of the Arabian Peninsula before Islam, just as the state of the Manathira and the Ghassanids had a role in their relationship with the Byzantine and Sasanian empires. In the battle of (Dhi Qar) around the year (611 AD) when they defeated the Sassanian forces in the battlefield and began raiding the western outskirts of their empire. As soon as the number of warriors and the tribesmen who joined them swelled, thinking began to establish a permanent Egypt to meet the growing needs of the warriors and organize their affairs.